Fusion bonding of thermosets composite structures with thermoplastic binder co-cure and prepreg interlayer in electrical resistance welding. (15th May 2016) - Xie, Lei; Liu, Hongbo; Wu, Wangqing; Abliz, Dilmurat; Duan, Yugang; Li, Dichen
Abstract: A new concept combining both thermoplastic binder co-cure and prepreg interlayer is proposed and investigated for fusion bonding of thermosets composite structures. Three different thermoplastic binders were co-cured respectively onto the surface of the carbon fiber reinforced epoxy (CF/Epoxy) composite laminates to form an auxiliary medium for electrical resistance welding. The carbon fiber reinforced binder (CF/Binder) prepreg interlayer, which is compression molded with a single layer of carbon fiber fabric sandwiched between two binder films, was designed as the heating element. Double cantilever beam (DCB) specimens were fabricated by fusion bonding of the CF/Epoxy composite laminates. The influence of the thermoplastic binders and the CF/Binder prepreg interlayers on the mode I interlaminar fracture toughness (GIC ) and the morphology of the fracture surface were studied respectively by double cantilever beam test and scanning electron microscope. The results indicate that a maximum average delamination strength GIC of 1879.6 J/m 2 was obtained in the case of the AX8900 binder welded specimens using twill weave fabric heating element. Three types of failure pattern can be visually and microscopically observed, i.e. interfacial-type failure, cohesive-type failure and interlaminar-type failure. Graphical abstract: Highlights: Thermoplastic binder co-cure and prepreg interlayer methods were integrated in fusion bonding Thermoplastic binder was co-cured onto the surface of the carbon fiber reinforced epoxy composite laminate The prepreg interlayer was designed as heating element made of carbon fiber reinforced binder prepreg The GIC of the fusion bonded specimens is significantly influenced by the binder and the heating element Three types of failure pattern in the fusion bonded specimens can be visually and microscopically observed.